2014
DOI: 10.1017/s1478951514000686
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of personhood at the end of life: The ring theory of personhood

Abstract: Our findings support the ring theory of personhood, which provides a clinically supported model of the conception of personhood that is context dependent and encompasses the four abovementioned aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 28 publications
(42 reference statements)
0
47
0
Order By: Relevance
“…The positioning of the nurse as the drawer also diverges from Krishna and Kwek’s Ring Theory of Personhood (Krishna & Kwek, 2015). In the Ring Theory of Personhood, the person at end-of-life determines which relationships are in the relational ring and which are in the societal ring (Krishna & Kwek, 2015). Although the transitory nature of who is in the circle mirrors the findings of this inquiry, adolescents and emerging adults do not choose who is part of the circle.…”
Section: Discussionmentioning
confidence: 99%
“…The positioning of the nurse as the drawer also diverges from Krishna and Kwek’s Ring Theory of Personhood (Krishna & Kwek, 2015). In the Ring Theory of Personhood, the person at end-of-life determines which relationships are in the relational ring and which are in the societal ring (Krishna & Kwek, 2015). Although the transitory nature of who is in the circle mirrors the findings of this inquiry, adolescents and emerging adults do not choose who is part of the circle.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the Ring Theory is believed to better capture the manner in which conceptions of personhood evolve over time and circumstances. (62)(63)(64)(65)(66) Echoing Krishna and Kwek's case study fi ndings, (83) Krishna and Alsuwaigh's study revealed that most palliative care patients placed more importance on their spirituality and legacy whilst reducing the importance of their conscious function as they progressed along their illness journey. (62) This increase in the relative importance of their respective Innate and Relational dimensions of personhood at the cost of their respective Individual ring is in keeping with data from Japan, the United States, Hong Kong and the Nordic nations, where similar evolutions in spiritual, social and individual beliefs and values have been documented.…”
Section: Triad Of Personhood-related Considerationsmentioning
confidence: 99%
“…(62) It also better contends with the evolution in goals of care and personal values and beliefs, as described in Krishna and Kwek's account of evolving concepts of personhood seen in the last months of life. (83) …”
Section: Triad Of Personhood-related Considerationsmentioning
confidence: 99%
“…5,6,11,27,28 This form of palliative sedation is accepted by most ethical points of view, cultural perspectives, and procedural guidelines. [8][9][10][28][29][30][31][32] ten Have and Welie 12 used the term mission creep to describe the intention of shortening life -however small -by using deep sedation, concluding that such an approach cannot be considered palliative sedation. In a clinical context, mission creep occurs when a specific practice considered appropriate in a given situation is gradually extended for use with different indications, groups of patients, and different intentions.…”
Section: Progressivementioning
confidence: 99%
“…22,28 The "innate" core of personhood ("individual component") has been suggested to persist even after relational and societal components are severely reduced. 29…”
Section: Ethical Considerationsmentioning
confidence: 99%